The Role of Audit Opinion as a Moderator of the Influence of ESG and GRC Disclosure on Market Reaction - Stiawan, I Kadek Jonh; Sinarwati, Ni Kadek; Musmini, Lucy Sri (Dinasti Publisher, 2025)
This study aims to analyze the influence of ESG and GRC disclosures on market reaction with audit opinion as a moderating variable. The research employs a quantitative research design with a population of banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample was selected using purposive sampling, resulting in 8 companies that met the criteria, with 5 years of observation yielding a total of 40 financial reports. Data collection was conducted through documentation studies and analyzed using Moderated Regression Analysis with panel data. The findings of this study indicate that ESG and GRC disclosures have a direct positive and significant effect on market reaction, whereas the audit opinion does not moderate the influence of ESG and GRC disclosures on market reaction. These findings are expected to be followed up by companies, particularly in the banking sector, to further optimize ESG and GRC disclosures in order to enhance investor confidence and gain a positive image in the public eye